An Approach to the Treatment of Children With COVID-19. Issue 8 (13th July 2022) - Boast, Alison; Curtis, Nigel; Holschier, Johanna; Purcell, Rachael; Bannister, Samantha; Plover, Christine; Chinnapan, Maidhili; Burgner, David; Boyce, Suzanne L.; McNab, Sarah; Gwee, Amanda; ,
Abstract : There are limited data to guide treatment recommendations for children with acute, symptomatic coronavirus disease 2019 (COVID-19). This review outlines a proposed management approach for children based on the published evidence to date and the approval of medications through drug regulatory agencies, as well as the known safety profile of the recommended drugs in this age group.